CRITICAL IMPRESSIONS ON AMIL PROFESSIONALIZATION AND ITS INFLUENCE ON CAREER INTENTIONS: A PLS-SEM APPROACH - Batubara, Maryam; Nasution, Juliana; Nasution, Muhammad Idris; Al Masri, Anas Zahir (EL DINAR: Jurnal Keuangan dan Perbankan Syariah, 2023)
The issue of professionalization of amil (zakat managers) still continues to occur in zakat organizations and has received strong criticism, including from students of the zakat and waqf management study program (MAZAWA). These criticisms include whether amil has become a full-time profession, education, training, and competency development for amil, the legitimacy of amil associations, the existence of a zakat amil code of ethics, as well as legal protection and the role of the state for the amil profession. This research aims to find out whether their critical impressions influence their intention to pursue a career as a professional amil. Conducted at UIN Sunan Ampel of Surabaya and IAIN Langsa, this research involved 95 respondents. Descriptive statistics and SEM-PLS via SmartPLS 4.0 software were used for data analysis. The results of the research showed that students' impressions of the professionalization of amil in Indonesia are in the medium category, which shows that there is still a lot of criticism towards it. But, their intention to pursue a career as amil remains high. Their perceptions significantly influence their career intentions; the better their perception, the higher their intention. By understanding how this professionalization can affect the efficiency, accountability and sustainability of zakat programs. Furthermore, it can increase the positive impact generated from the distribution of zakat funds.